Unconventional monetary policy in the euro area: A tale of three shocks - Luca Fanelli; Antonio Marsi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
High-frequency (HF) surprises of relevant asset prices around central bank meetings are extensively employed in the literature to identify the effects of conventional/unconventional monetary policy. This identification strategy assumes that these surprises reflect either a single unconventional 'monetary shock' or, as recently suggested, jointly an unconventional monetary shock and a central bank 'information shock'. In this paper we show that monetary policy in the euro area after 2008 is best characterized by three shocks, not two. Besides the unconventional monetary shock and the information shock, we consider a third shock resulting from the ECB directly managing fragmentation risk in the sovereign bond market. We call this additional shock 'spread shock', and show that it permits to solve a puzzle we observe in HF comovement of long term risk free rates and sovereign spreads around press conferences. We identify the dynamic causal effects produced by the three shocks through a proxy-SVAR methodology which, using HF surprises of the euro area risk-free yield curve, stock prices and sovereign spreads, combines sign-restrictions with narrative restrictions and then extracts external variables (instruments) from an admissible identification set. Empirical results, obtained through a daily proxy-SVAR and Local Projections based on monthly data, reveal that the spread shock represents an important ingredient of the transmission mechanism of the monetary policy after the Global Financial Crisis. It reflects ECB's attempt to offset self-fulling expectations of default in the euro area sovereign debt markets and behaves as a complement, not a substitute of the information shock.
Keywords: E43; E44; E52; E58; G10; 330; European Central Bank; Monetary Policy Shock; Proxy-SVAR; Spread Shock